2018
DOI: 10.4018/ijkm.2018100103
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation of Psychological Capital in the Relationship of Perceived Organizational Support, Engagement and Extra-Role Performance

Abstract: Organizations become vulnerable to the loss of the tacit and explicit knowledge when employees leave the organization. To mitigate this loss, organizations adopt flexible labor model, where employees are managed as flexible workers. But, engaging these workers becomes another challenge for the organization, as due to limited interaction they are less attached with the organization. Data is collected from 212 insurance agents of India and structural equation modeling (SEM) was done to analyse the responses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We can conclude that OC could be considered a PsyCap antecedent that can include the following identified in the research factors: compassion experienced in the workplace (Ko & Choi, 2019); supportive climate (Luthans et al, 2008c); learning climate (Pitichat et al, 2018); POS (Erdem et al, 2017; Liu et al, 2013; Newman et al, 2018; Pitichat et al, 2018; Roemer & Harris, 2018; Shaheen & Krishnankutty, 2018; Wang et al, 2017); perceived supervisor support (Newman et al, 2018); job autonomy (Mazzetti et al, 2016; Choi, 2020); coworker support (Mazzetti et al, 2016); organizational innovation climate (Hsu & Chen, 2017); and service climate (Kang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We can conclude that OC could be considered a PsyCap antecedent that can include the following identified in the research factors: compassion experienced in the workplace (Ko & Choi, 2019); supportive climate (Luthans et al, 2008c); learning climate (Pitichat et al, 2018); POS (Erdem et al, 2017; Liu et al, 2013; Newman et al, 2018; Pitichat et al, 2018; Roemer & Harris, 2018; Shaheen & Krishnankutty, 2018; Wang et al, 2017); perceived supervisor support (Newman et al, 2018); job autonomy (Mazzetti et al, 2016; Choi, 2020); coworker support (Mazzetti et al, 2016); organizational innovation climate (Hsu & Chen, 2017); and service climate (Kang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A study in French Air Force revealed the positive relationship between POS and elements of engagement like vigor, dedication, and absorption (Gillet et al, 2017). Past studies provided empirical evidence regarding the positive relationship between POS and employee engagement (Bailey et al, 2015;Shantz et al, 2014;Murthy, 2017;Shaheen & Krishnankutty, 2018). Thus, our study posits that H2: POS will positively affect employee engagement.…”
Section: The Effect Of Hr Practice and Perceived Organizational Suppomentioning
confidence: 56%
“…Results by Dai & Qin (2016) shows that POS impact is higher when is combined with organizational identification. Wang, Liu, Zou, Hao, & Wu (2017) and Shaheen & Krishnankutty (2018) has pointed out that psychological capital helps to mediate between POS and work engagement. Future research lines could address relationship between both variables using other factors to broaden the perspective of interaction in Latin American context.…”
Section: Discussionmentioning
confidence: 99%